Co-creation: A new keyword in advancing the objectives of health organizations in COVID-19 crisis - Shahram Salavati; Flora Rahimaghaee; Khatere Seylani (Tehran University of Medical Sciences, 2021)
A quick look at the published literature on COVID-19 disease reveals predictions that indicate more infected patients will be admitted to hospitals and clinics. Although much attention has been paid to the challenges of caring for a sharp increase in the number of infected people, less attention has been paid to patients who are at the beginning of their recovery. Accepting the responsibility of treatment by patients not only benefits them but also helps hospitals. Patients' cooperation can prevent the spread of disease, both in terms of cross-contamination and control and treatment. The literature points to the positive role of clients and their impact, which can be called co-creation, and considers it effective in organizational development. Co-creation improves patients' therapeutic outcomes and increases their respect and value for the organization. In situations such as the COVID-19 pandemic in health care organizations, the perceived shared value of patients is effective in their participation in self-care.